Possible signal of an exotic $$I=1$$ I = 1 , $$J=2$$ J = 2 state in the $$B → D^{*-}D^+K^+$$ B → D ∗ - D + K + reaction - Wen-Tao Lyu; Man-Yu Duan; Chu-Wen Xiao; En Wang; Eulogio Oset (European Physical Journal C: Particles and Fields)
Abstract We study the $$B^+ → D^{*-}D^+K^+$$ B + → D ∗ - D + K + reaction, showing that a peak in the $$D^+K^+$$ D + K + mass distribution around $$2834 \text { MeV}$$ 2834 MeV reported by LHCb could be associated with a theoretical exotic state with that mass, a width of $$19 \text { MeV}$$ 19 MeV and $$J^P=2^+$$ J P = 2 + , stemming from the interaction of the $$D^{*+}K^{*+}$$ D ∗ + K ∗ + and $$D^{*+}_s ρ ^+$$ D s ∗ + ρ + channels, which is a partner of the $$0^+$$ 0 + $$T_{c{\bar{s}}}(2900)$$ T c s ¯ ( 2900 ) . We show that the data is compatible with this assumption, but also see that the mass distribution itself cannot discriminate between the spins $$J=0$$ J = 0 , 1, 2 of the state. Then we evaluate the momenta of the angular mass distribution and show that they are very different for each of the spin assumptions, and that the momenta coming from interference terms have larger strength at the resonant energy than the peaks seen in the angular integrated mass distribution. We make a call for the experimental determination of these magnitudes, which has already been used by the LHCb in related decay reactions.